2016
DOI: 10.1177/0309133316650617
|View full text |Cite
|
Sign up to set email alerts
|

A review of snow in Britain

Abstract: Climate change is likely to have a significant effect on snow globally, with most effect where current winter temperatures are close to 0°C, including parts of upland Britain. There is evidence of decreasing trends in observations of snowfall and lying snow in Britain, and climate projections suggest a continuation of this trend. Although river flows in Britain are generally dominated by rainfall rather than snowmelt, some upland catchments have a significant snowmelt contribution. There is evidence of changes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 115 publications
(248 reference statements)
0
11
0
Order By: Relevance
“…The lack of significance in the trend analysis of precipitation has also been reported in these studies [80][81][82][83][84], with higher decreasing trend values observed during the 21st century under semiarid conditions (e.g., −9% and −19% for RCPs 4.5 and 8.5, respectively, in the Chilean Andes and −1.5% and −5.5% for RCPs 4.5 and 8.5, respectively, in Sierra Nevada). These results also show how apparent decreases of snowfall are expected in all future scenarios [74,76,80,81,[85][86][87], with a higher loss of snowfall amount in areas above 1500 m a.s.l. but a larger impact in lower areas were snowfall might not even occur in the future [74,76,86].…”
Section: Discussionmentioning
confidence: 58%
“…The lack of significance in the trend analysis of precipitation has also been reported in these studies [80][81][82][83][84], with higher decreasing trend values observed during the 21st century under semiarid conditions (e.g., −9% and −19% for RCPs 4.5 and 8.5, respectively, in the Chilean Andes and −1.5% and −5.5% for RCPs 4.5 and 8.5, respectively, in Sierra Nevada). These results also show how apparent decreases of snowfall are expected in all future scenarios [74,76,80,81,[85][86][87], with a higher loss of snowfall amount in areas above 1500 m a.s.l. but a larger impact in lower areas were snowfall might not even occur in the future [74,76,86].…”
Section: Discussionmentioning
confidence: 58%
“…However, the limited availability of historical daily minimum and maximum temperature data meant that a snow module could not be applied prior to 1960. Kay (2016) notes that snow can have a significant effect on river flows in some parts of Scotland, enhancing flows in spring and into summer (during snowmelt), with lower summer flows occurring in years with less snow cover. In the late 19 th and early 20 th century, when average temperatures were lower and thus there was more snow, this seasonal flow pattern is likely to have been more prevalent in other parts of Britain too.…”
Section: Drought Identification (1891-2015)mentioning
confidence: 99%
“…Under rapid climate change, hydrological processes, including snowmelt processes, have been greatly affected (Pachauri et al, 2014;Wu et al, 2018). A series of hydrological responses to temperature and precipitation change, including time shifts and volume changes in springtime snowmelt discharge, have been observed over the past few years in many regions, including North America (Stewart et al, 2004(Stewart et al, , 2009Tang et al, 2019), the Tibetan Plateau (Immerzeel et al, 2010), Europe (Kay, 2016), and central Asia (Yucel et al, 2015); thus, the accurate evaluation of snowmelt contributions will be increasingly important in the future.…”
Section: Introductionmentioning
confidence: 99%